Expression of IL-4 and IL-12 in the aqueous humor of patients with chronic primary angle-closure glaucoma - Feng, Qi; Shen, Jiang; Zhang, Li; Wang, Qiong; Luo, Surong; Luo, Man; Chen, Wei (Frontiers in Medicine, 2024)
Introduction Angle-closure glaucoma is a common type of glaucoma in Asian populations. However, the role of inflammatory cytokines in angle-closure glaucoma is yet to be elucidated. Therefore, this study aimed to examine the expression of interleukin-4 (IL-4) and IL-12 in the aqueous humor of patients with chronic primary angle-closure glaucoma (CPACG) and elucidate the correlations between IL-4 and IL-12 concentrations in the aqueous humor, the degree of visual field defects, and retinal nerve fiber layer (RNFL) thickness in patients with CPACG. Methods Aqueous humor samples were obtained from 31 patients diagnosed with CPACG at the Shaoxing People’s Hospital between April 2022 and March 2023 and from 30 individuals with cataract (control). Based on the degree of the mean defect (MD), patients were divided into three groups: group A (MD ≤ −6dB, n= 10), group B (−6dB< MD< −12dB, n= 9), and group C (MD ≥ − 12dB, n= 12). RNFL thickness was measured using an optical coherence tomograph, and the concentrations of IL-4 and IL-12 in the aqueous humor were measured using Luminex technology. Results Aqueous humor concentration of IL-4 was significantly higher (p = 0.036) in the CPACG group than in the cataract group. However, there was no significant difference (p > 0.05) in IL- 12 concentration between the two groups. Additionally, there were no significant differences (p > 0.05) in IL-4 and IL-12 levels among patients with varying degrees of visual field defects (groups A, B, and C). Spearman’s correlation analysis showed that IL-4 and IL-12 concentrations were not correlated (p > 0.05) with RNFL thickness around the optic disc and the degree of visual field defects. Discussion Conclusively, IL-4 may play an important role in the pathogenesis of CPACG. Given that IL-4 and IL-12 concentrations in the aqueous humor were not significantly correlated with RNFL thickness and the degree of visual field defects, the increase in IL-4 and IL-12 expression may not induce apoptosis and loss of retinal ganglion cells or affect RNFL thickness as well as the degree of visual field defects.